GROUNDS FOR LIMITING THE PROPERTY RIGHTS OF THE SUSPECTED, ACCUSED AND OTHER PERSONS DURING THE TEMPORARY WITHDRAWAL OF ELECTRONIC INFORMATION SYSTEMS OR THEIR PARTS, MOBILE TERMINALS OF COMMUNICATION SYSTEMS - Літвінова, Ірина Феофанівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the actual and formal legal grounds for restricting the property rights of the suspect, accused and other persons during the temporary seizure of electronic information systems or their parts, mobile terminals of communication systems are investigated. Methods: in the author’s opinion, the changes introduced in the Criminal Procedural Code of Ukraine in 2017 on the issues of temporary seizure of electronic information systems or their parts, mobile terminals of communication systems, instead of settling the existing problematic issues in this area, brought additional contradictions to the main law that regulated the procedure for criminal proceedings on the territory of Ukraine. Discussion: the necessity of revision of the procedural order of temporary withdrawal of electronic information systems or their parts, mobile terminals of communication systems with the purpose of eliminating existing contradictions in the legislation and its harmonization on these issues is substantiated.